Nfatc4 Deficiency Attenuates Ototoxicity by Suppressing Tnf-Mediated Hair Cell Apoptosis in the Mouse Cochlea - Zhang, Yanping; Chen, Diyan; Zhao, Liping; Li, Wen; Ni, Yusu; Chen, Yan; Li, Huawei (Frontiers in Immunology, 2019)
The loss of sensory hair cells in the cochlea is the major cause of sensorineural hearing loss, and inflammatory processes and immune factors in response to cochlear damage have been shown to induce hair cell apoptosis. The expression and function of Nfatc4 in the cochlea remains unclear. In this study, we investigated the expression of Nfatc4 in the mouse cochlea and explored its function using Nfatc4−/− mice. We first showed that Nfatc4 was expressed in the cochlear hair cells. Cochlear hair cell development and hearing function were normal in Nfatc4−/− mice, suggesting that Nfatc4 is not critical for cochlear development. We then showed that when the hair cells were challenged by ototoxic drugs Nfatc4 was activated and translocated from the cytoplasm to the nucleus, and this was accompanied by increased expression of Tnf and its downstream targets and subsequent hair cell apoptosis. Finally, we demonstrated that Nfatc4-deficient hair cells showed lower sensitivity to damage induced by ototoxic drugs and noise exposure compared to wild type controls. The Tnf-mediated apoptosis pathway was attenuated in Nfatc4-deficient cochlear epithelium, and this might be the reason for the reduced sensitivity of Nfatc4-deficient hair cells to injury. These findings suggest that the amelioration of inflammation-mediated hair cell apoptosis by inhibition of Nfatc4 activation might have significant therapeutic value in preventing ototoxic drug or noise exposure-induced sensorineural hearing loss.